2017
DOI: 10.1038/s41598-017-16383-5
|View full text |Cite
|
Sign up to set email alerts
|

Elite long jumpers with below the knee prostheses approach the board slower, but take-off more effectively than non-amputee athletes

Abstract: The use of technological aids to improve sport performance (‘techno doping’) and inclusion of Paralympic athletes in Olympic events are matters of ongoing debate. Recently, a long jumper with a below the knee amputation (BKA) achieved jump distances similar to world-class athletes without amputations, using a carbon fibre running-specific prosthesis (RSP). We show that athletes with BKA utilize a different, more effective take-off technique in the long jump, which provided the best athlete with BKA a performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…Full body kinematics and GRFs (1,000 Hz, AMTI Inc., Watertown, MA) were collected synchronously using a markerbased motion capture system (11 MX-13 cameras, 200 Hz, Vicon, Oxford, UK) in order to perform biomechanical modeling. A total of 42 spherical reflective markers were placed on the participants' body segments in accordance to the ALASKA Dynamicus protocol (ALASKA, INSYS GmbH, Germany) (Härtel and Hermsdorf, 2006;Willwacher et al, 2017). Prior to the attachment of the data collection equipment, standardized anthropometric measurements were exhibited.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Full body kinematics and GRFs (1,000 Hz, AMTI Inc., Watertown, MA) were collected synchronously using a markerbased motion capture system (11 MX-13 cameras, 200 Hz, Vicon, Oxford, UK) in order to perform biomechanical modeling. A total of 42 spherical reflective markers were placed on the participants' body segments in accordance to the ALASKA Dynamicus protocol (ALASKA, INSYS GmbH, Germany) (Härtel and Hermsdorf, 2006;Willwacher et al, 2017). Prior to the attachment of the data collection equipment, standardized anthropometric measurements were exhibited.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…The 3D marker coordinates and GRF data were reconstructed and filtered with a 15 Hz low-pass filter (zero-phase Butterworth 4th order) (Kristianslund et al, 2012). Inverse dynamics modeling was performed using the full-body Dynamicus 9 model (Härtel and Hermsdorf, 2006;Willwacher et al, 2017). Each participant was individually scaled to the generic linkedsegment model using the measured anthropometrics and the static calibration trial (Whittlesey and Robertson, 2014).…”
Section: Biomechanical Modelmentioning
confidence: 99%
“…Several studies reported that athletes with transtibial amputation wearing RSPs have asymmetrical vertical ground reaction force (GRF) and joint kinetics between prosthetic (PST) and intact (INT) legs across a wide range of speeds from 3.0 m/s up to top speed (Beck et al, 2017; Buckley, 2000; Grabowski et al, 2010; McGowan et al, 2012; Willwacher et al, 2017). For transfemoral amputees, a previous study demonstrated that unilateral transfemoral amputees wearing RSPs exhibited smaller vertical and braking components of GRFs for the PST than the INT during maximal sprinting (Makimoto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Evading detection of the use of prohibited substances or methods of doping has been attempted by chemical or physical manipulation of doping control samples in the past, some of which were identified predominantly by abnormal profiles observed in the steroidal module of the ABP . Whether or not ruthless individuals would consider irreversible orthopedic interventions in expectation of gaining a competitive edge is yet unclear, but the scenario cannot be fully excluded as the temptation to modify genetic material has been discussed also in the past.…”
Section: Chemical and Physical Manipulation/gene Dopingmentioning
confidence: 99%
“…A different approach aiming at quantifying red blood cell microparticles (RBC-MPs) formed during storage of whole blood in conventional CPDA-1 blood bags was pursued by Voss et al 126 tive edge is yet unclear, 129,130 but the scenario cannot be fully excluded as the temptation to modify genetic material has been discussed also in the past.…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%